2021
DOI: 10.3390/ijms222312972
|View full text |Cite
|
Sign up to set email alerts
|

Sanguiins—Promising Molecules with Broad Biological Potential

Abstract: Compounds of natural origin, an infinite treasure of bioactive chemical entities, persist as an inexhaustible resource for discovering new medicines. In this review, we summarize the naturally occurring ellagitannins, sanguiins, which are bioactive constituents of various traditional medicinal plants, especially from the Rosaceae family. In-depth studies of sanguiin H-6 as an antimicrobial, antiviral, anticancer, anti-inflammatory, and osteoclastogenesis inhibitory agent have led to potent drug candidates. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Ellagitannins are plant secondary metabolites that tend to form relatively high molecular weight dimers and oligomers, ranging from 300 to 20,000 Da. Plants from the Rosaceae family accumulate a series of oligomeric, macrocyclic oligomeric, and C -glycosidic ellagitannins that can be used as chemophenetic markers ( Grochowski et al, 2017 ; Gesek et al, 2021 ). On several occasions the presence of dimeric ellagitannin - agrimoniin in aerial parts of Potentilla species, in particular P. anserina and P. kleiniana, P. recta , have been reported ( Okuda et al, 1982 ; Fecka, 2009 ; Bazylko et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ellagitannins are plant secondary metabolites that tend to form relatively high molecular weight dimers and oligomers, ranging from 300 to 20,000 Da. Plants from the Rosaceae family accumulate a series of oligomeric, macrocyclic oligomeric, and C -glycosidic ellagitannins that can be used as chemophenetic markers ( Grochowski et al, 2017 ; Gesek et al, 2021 ). On several occasions the presence of dimeric ellagitannin - agrimoniin in aerial parts of Potentilla species, in particular P. anserina and P. kleiniana, P. recta , have been reported ( Okuda et al, 1982 ; Fecka, 2009 ; Bazylko et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols and their four main categories: flavonoids, phenolic acids, lignans, and stilbenes are among the most well-known phytochemicals [ 1 , 9 , 23 ]. They are best-known for their antioxidant properties, but the range of their activity is much wider [ 2 , 23 ]. Many pre-clinical and clinical (both observational and intervention) studies have suggested, that increased intake of phenolic compounds is related to a lower risk of cardiovascular diseases, diabetes, cancer, and neurodegenerative diseases [ 24 , 25 , 26 , 27 ].…”
Section: Chemical Content Of Seedsmentioning
confidence: 99%
“…For example, sanguiin H-6 is a hydrolyzable tannin abundant in blackberry seeds. It shows a wide array of biological activities, including antioxidant, antibacterial, antitumor, anti-angiogenic, estrogenic, and anti-osteoclastogenic [ 2 , 48 , 49 , 50 , 51 , 52 ]. Condensed tannins are oligomers or polymers of flavan-3-ol linked through an interflavan carbon bond.…”
Section: Chemical Content Of Seedsmentioning
confidence: 99%
See 2 more Smart Citations